Ultra scale‐down characterization of the impact of conditioning methods for harvested cell broths on clarification by continuous centrifugation—Recovery of domain antibodies from rec E. coli. Issue 5 (28th December 2013) - Chatel, Alex; Kumpalume, Peter; Hoare, Mike
ABSTRACT The processing of harvested E. coli cell broths is examined where the expressed protein product has been released into the extracellular space. Pre‐treatment methods such as freeze–thaw, flocculation, and homogenization are studied. The resultant suspensions are characterized in terms of the particle size distribution, sensitivity to shear stress, rheology and solids volume fraction, and, using ultra scale‐down methods, the predicted ability to clarify the material using industrial scale continuous flow centrifugation. A key finding was the potential of flocculation methods both to aid the recovery of the particles and to cause the selective precipitation of soluble contaminants. While the flocculated material is severely affected by process shear stress, the impact on the very fine end of the size distribution is relatively minor and hence the predicted performance was only diminished to a small extent, for example, from 99.9% to 99.7% clarification compared with 95% for autolysate and 65% for homogenate at equivalent centrifugation conditions. The lumped properties as represented by ultra scale‐down centrifugation results were correlated with the basic properties affecting sedimentation including particle size distribution, suspension viscosity, and solids volume fraction. Grade efficiency relationships were used to allow for the particle and flow dynamics affecting capture in the centrifuge. The size distribution below a critical diameter dependant on the broth pre‐treatment type was shown to be the main determining factor affecting the clarification achieved. Biotechnol. Bioeng. 2014;111: 913–924. © 2013 The Authors. Biotechnology and Bioengineering Published by Wiley Periodicals, Inc.